479 Effects of extracellular matrix on pacemaking cardiomyocyte function - Brian Howard; Regan Smithers; Kaitlin Van Brusselen; Hillary K.J. Kao; Deborah K. Lieu (Journal of Clinical and Translational Science)
Objectives/Goals: The extracellular matrix (ECM) of the sinoatrial node (SAN) is critical for maintaining automaticity in hiPSC-derived pacemaking cardiomyocytes (PCMs) under cyclic strain. We aim to determine the ECM ligands responsible for cell-ECM mediated mechanotransduction and the resulting phenotype in PCMs. Methods/Study Population: HiPSCs are differentiated to PCM and replated on substrate with 5 or 15 kPa PDMS that are coated with 5 or 25 ug/cm of either collagen I or fibronectin at sub-confluent density to restrict junction engagement to only costameres. Then, PCM are subjected to 10% cyclic mechanical strain at 1 Hz for 48 hours, with static culture as control. PCMs from all conditions are subsequently fixed and stained for cardiomyocyte-specific troponin T (TnT), pacemaking HCN4 channel, and pro-pacemaking transcription factors (Shox2, Isl1, Tbx3, Tbx18). Additionally, PCM cell size will also be assessed. Results/Anticipated Results: Considering the amount of hypertrophy and myofilament in CMs correlates with mechanical strain, we expect a reduced degree of mechanotransduction in hiPSC-PCM on collagen I with a stiffness 15 kPa to induce smaller cell size with fewer myofilament and an upregulation of HCN4 and pro-pacemaking transcription factors than those on 5 kPa and those on fibronectin of either 5 or 15 kPa after cyclic strain. This is because COL1 is reported to have a lower signaling threshold but a limited sensitivity to force which contributes to the diminished mechanotransduction signaling. Discussion/Significance of Impact: Effects of the microenvironment on hiPSC-PCMs via costamere mechanotransduction may provide insights for engineering biopacemakers with a suitable ECM, to potentially preserve automaticity in hiPSC-PCMs and sustain long-term pacemaking function, making biopacemakers a step closer to reality.